ANALISIS KEBUTUHAN ALAT EKSPERIMEN FISIKA LIFT SEDERHANA UNTUK MATERI HUKUM NEWTON DI SMAN 6 KOTA BENGKULU - Arumningrum, Bunga D; Utami, Cindi N; Gunawan, Bodi (UNIB Press, 2025)
The research carried out at SMAN 6 Bengkulu City aims to analyze the need for physics experiment tools, especially on Newton's Law material. The lack of availability of physics experimental equipment during the learning process makes it difficult for students to understand the concept of Newton's laws. The method used in this research is a mix method, namely quantitative and qualitative. Data collection technique in the form of qualitative interviews with physics teachers and quantitative questionnaires with students. Meanwhile, the instrument used in the research was a sheet teacher interviews and student questionnaire sheets. The results of the interviews and questionnaires obtained were that students had an interest in studying physics of 88.5% and felt that studying using physics experimental tools could understand the concept of Newton's law, but teachers rarely used physics experimental tools in Law material Newton due to difficulties in access from the lab to the classroom. This makes students feel bored with the learning methods used by teachers at 84.6% and there are still concepts that are not understood in Newton's law material at 69.2%